Massrearing establishment and dispersal of Pseudaphycus maculipennis a biocontrol agent for obscure mealybug - Charles, J.G.; Allan, D.J.; Rogers, D.J.; Cole, L.M.; Shaw, P.W.; Wallis, D.R. (New Zealand Plant Protection, 2004)
Approximately 750000 P maculipennis (internal facultatively gregarious encyrtid parasitoids of the obscure mealybug (Pseudococcus viburni)) were released to 41 pipfruit orchards in Hawkes Bay Nelson/Motueka and Auckland and to the Wellington Botanic Gardens between 2001 and 2004 At least a year later they were recovered from 83 of the Hawkes Bay and 60 of the Nelson orchards and from the Wellington Botanic Gardens indicating that the parasitoid has a solid foothold in New Zealand Pseudaphycus maculipennis have dispersed since their release at a natural rate of about 200 m/year Laboratory massrearing production techniques for P maculipennis are described No measures of the impact of P maculipennis on obscure mealybug populations in orchards have yet been carried out